Malignant glomus tumor of jejunum with liver and peritoneum metastasis: a rare case report - Peng, Shilan; Yang, Nan; Xu, Zifan; Su, Guomiao; Tuo, Xiaoyu; Liu, Shiyue; Lei, Zi; Pan, Guoqing (Frontiers in Oncology, 2025)
Glomus tumors (GTs) are rare mesenchymal neoplasms that occur predominantly on the subungual region of the distal extremities and are rarely seen in visceral organs such as the gastrointestinal tract. Malignant glomus tumors (MGTs) is even more rare, comprising less than 1% of all GTs. We reported an 82-year-old female patient with MGTs of the jejunum, accompanied by metastases to the liver and peritoneum. The patient presented with a primary complaint of epigastric pain with nausea and acid reflux for two months. Computed tomography scan revealed a prominently enhanced, inhomogeneous-density mass in the jejunum, the nature of which—benign or malignant—could not initially be determined. Postoperative pathological diagnosis confirmed the lesion to be a jejunal MGT. Regrettably, the patient declined additional treatment, subsequently developing liver and peritoneal metastases one year later. She eventually died within 18 months of initial diagnosis. This report summarizes the clinical and histopathological features of jejunal MGTs with the aim of increasing awareness among clinicians and pathologists regarding this disease.